2010
DOI: 10.1016/j.paid.2010.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of a short form of the Affective Lability Scale (ALS-18)

Abstract: Psychometric properties of a short form of the Affective Lability Scale (ALS) that was developed in a nonclinical sample (i.e., undergraduate students) were examined in a sample of people diagnosed with Cluster B DSM-IV Axis II personality disorders (n=236), other personality disorders (n=180), and healthy comparison participants (n=164). The total score of the ALS-18 score correlated strongly with the original 54-item scale (r = .97) and aspects of convergent and discriminant validity of the ALS-18 subscales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 17 publications
9
34
1
Order By: Relevance
“…The short version also showed high internal consistency (Alpha values between 0.77 and 0.88). ALS-54 and ALS-18 also correlated highly (ρ¼0.97, p o0.001), as similarly reported in the study by Look et al (2010). Confirmatory Factor Analysis demonstrated somewhat equal fit of the data for ALS-18 and ALS-54.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The short version also showed high internal consistency (Alpha values between 0.77 and 0.88). ALS-54 and ALS-18 also correlated highly (ρ¼0.97, p o0.001), as similarly reported in the study by Look et al (2010). Confirmatory Factor Analysis demonstrated somewhat equal fit of the data for ALS-18 and ALS-54.…”
Section: Discussionsupporting
confidence: 84%
“…Our study confirmed the utility of also using the short form in clinical groups characterized by high levels of affective dysregulation, such as patients with bipolar disorders (Aminoff et al, 2012;Etain et al, 2008). Similar to the study by Look et al (2010) of patients with personality disorders, and the original validation paper by Oliver and Simons (2004), our results demonstrate good validity and internal consistency of ALS-18 measuring affective lability. Our study is the largest study to compare ALS-18 to the original ALS-54, and the first study to investigate the use of ALS-18 in a group of patients with bipolar disorders and their first-degree relatives.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations